Synthesis and Anti-Mycobacterium tuberculosis Evaluation of Aza-Stilbene Derivatives - Pavan, Fernando Rogério [UNESP] (2011)
Tuberculosis (TB) is a truly global disease, found in every country on earth. One-third of humanity, over 2 billion people, carry the bacillus that causes TB and 2 million people die of the disease each year. Despite that, no new specific drug against Mycobacterium tuberculosis has been developed since the 1960s. There are several candidates for new anti-TB agents, but none proven clinically effective. Stilbenes are compounds found in numerous medicinal plants and food products with some known biological and even antimycobacterial activity. This paper describes the synthesis and the anti-M. tuberculosis activity of eight stilbene analogues. The synthesis and characterization of these compounds are shown, and the results compared with one "first"-line drug used in current therapy.